Suggested methodology for rehabilitation of ancient masonry castles and forts on rock - António Joaquim Pereira Viana da Fonseca (2014)
Forts, including in this designation military castles, present high complexity due to their nature. Methodologies followed in the rehabilitation of forts are briefly presented, with the emphasis on characterization of materials and rock masses and on tests and numerical models developed for ancient forts. Studies concerning forts with Portuguese legacy are presented. The first case is related with rehabilitation of foundations and walls of the Guimarães Castle, Portugal. The causes of the appearance of holes or torn threads in the exposed face of the wall and the tower of the extreme southwest of the castle were assessed. The intervention performed was focused on the stabilization of the rock mass and careful sealing of discontinuities in the high strength rock mass and consolidation of the most weathered fractured rock mass. The second case is related to forts existing at Muscat, Oman. The protection of the Jalali Fort is studied in detail. During 2007, cyclone Gonu caused substantial damage to the seawall adjacent to the fort. The study addresses the redesign of the seawall. Keywords: masonry forts, rehabilitation, rock mechanics, Guimarães Castle, Jalali Fort.